UJI FITOKIMIA DAN BIOAKTIVITAS DAUN KATUK HUTAN (Phylanthus reticulatus var. Glaber) - ARMANSYAH K. RACHIM; SUSILO BUDI HUSODO; MULIYANA ARIFUDIN (JURNAL KEHUTANAN PAPUASIA, 2020)
This study aims to determine the content of phytochemicals and bioactivity properties of antioxidant, antibacterial, and toxicity of the methanol extract of Phylanthus reticulatus var. Glaber leaf. The testing method used is the phytochemical testing, testing antioxidant, antibacterial testing dan toxicity testing. The test results show that phytochemical extracts of Phylanthus reticulatus var. Glaber leaves contain alkaloids, flavonoids, and triterpenoids. An antioxidant test reveals that the concentration of 25, 50, and 100 ppm of the extract at prohibits free radical DPPH respectively around 79, 81 dan 89%. The antibacterial testing extracts of Phylanthus reticulatus var. Glaber leaves show that it does not have the antibacterial property. The toxicity test shows that this extract does not have toxicity activity.